STRATEGI PENINGKATAN KUALITAS PENDIDIKAN DI MADRASAH ALIYAH KABUPATEN SIDRAP: Tinjauan Implementasi Kurikulum Tingkat Satuan Pendidikan - Ali Rahim (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2015)
Abstract:This study aimed to analyze the strategy of improving the quality of education in Madrasah Aliyah Sidrap viewed from of the implementation of the educational unit level curriculum. This type of research was qualitative. The data collection methods used were observation, interviews, documentation and the data analysis techniques used were data reduction, data display and data verification. The results of the research showed that; 1) The teachers of MA in general had implemented the educational unit level curriculum. 2) Most of the teachers were not optimal in implementing it because the condition, did not support. 3) The supporting factors were the headmaster management, the curriculum, the teachers’ competence, the educational budget, the optimization of cooperation with the community. 4) The inhibiting factors were lack of infrastructure, the teachers who teach were not in accordance with their educational background, and lack of teachers' welfare. 5) The efforts conducted to overcome the inhibiting factor was to improve the quality of infrastructure. 6) The kind of strategies used were, improving the quality of the curriculum management and the teaching programs, increasing the teachers’ competence, improving the welfare of the teachers, increasing students’ achievement, fulfilling facilities and infrastructure, improving the quality of implementation of headmaster’s role, improving the quality of devotion to God Almighty and noble character, and improving the management of the Islamic school relationship with the community.Abstrak:Penelitian ini bertujuan untuk menganalisis strategi peningkatan kualitas pendi-dikan Madrasah Aliyah di Kabupaten Sidrap ditinjau dari segi implementasi ku-rikulum tingkat satuan pendidikan. Jenis penelitian adalah penelitian kualitatif. Metode pengumpulan data adalah; observasi, wawancara, observasi dan penelu-suran referensi dengan teknik analisis data reduksi data, penyajian data dan veri-fikasi data. Hasil penelitian menunjukkan; 1) Umumnya guru MA sudah meng-implementasikan KTSP. 2) Sebagian guru tidak maksimal karena kondisi sarana yang tidak mendukung. 3) Faktor pendukung yaitu; manajemen kepala madra-sah, kurikulum, kompetensi guru, anggaran pendidikan, optimalisasi kerjasama dengan masyarakat. 4) Faktor penghambat; kurangnya sarana prasarana, guru mengajar tidak sesuai dengan latar belakang pendidikannya, rendahnya kesejah-teraan guru. 5) Untuk mengatasi faktor penghambat adalah; meningkatkan kuali-tas sarana prasarana. 6) Bentuk strategi yaitu; peningkatan kualitas manajemen kurikulum dan program pengajaran, peningkatan kompetensi guru, peningkatan kesejahteraan guru, peningkatan prestasi akademik siswa, terpenuhinya kebu-tuhan sarana dan prasarana, peningkatan kualitas pelaksanaan tugas kepala madrasah, peningkatan kualitas ketakwaan kepada Allah swt. serta akhlak mulia, dan meningkatkan manajemen hubungan madarasah dengan masyarakat.